Construction and characterization of a bacteriophage T4 DNA polymerase deficient in 3'-->5' exonuclease activity. - Frey, M W (1993)
Bacteriophage T4 DNA polymerase has a proofreading 3'-->5' exonuclease that plays an important role in maintaining the accuracy of DNA replication. We have constructed a T4 DNA polymerase deficient in this exonuclease by converting Asp-219 to Ala. The exonuclease activity of the mutant T4 DNA polymerase has been reduced by a factor of at least 10(7), but it retains a polymerase activity whose kinetic parameters, kcat, Kd DNA, and Kd dATP, are very close to those of the wild-type enzyme. Bacteriophage T4 with the mutant polymerase gene has a markedly increased mutation frequency. Asp-219 in T4 DNA polymerase is within a sequence similar to those surrounding Asp residues previously shown to be essential for the exonuclease activities of the Klenow fragment of Escherichia coli DNA polymerase I (Asp-424), bacteriophage phi 29 DNA polymerase (Asp-66), and Saccharomyces cerevisiae DNA polymerase delta (Asp-405). Thus, these studies support the proposal that there are similar sequences in the active sites for the proofreading exonucleases of these and related DNA polymerases.